A comprehensive update of ICET-A Network on COVID-19 in thalassemias: what we know and where we stand - De Sanctis, Vincenzo; Canatan, Duran; Corrons, Joan Lluis Vives; Karimi, Mehran; Daar, Shahina; Kattamis, Christos; Soliman, Ashraf T; Wali, Yasser; Alkindi, Salam; Huseynov, Valeh; Nasibova, Afag; Tiryaki , Tarık Onur; et al. (Acta Biomedica Atenei Parmensis, 2020)
A review of the literature on COVID-19 pandemic in patients with thalassemias is presented. Globally, the prevalence of COVID-19 among  β-thalassemia patients seems to be lower than in general population; associated co-morbidities aggravated the severity of  COVID- 19, leading to a poorer prognosis, irrespective of age. A multicenter registry will enhance the understanding of COVID-19 in these patients and will lead to more evidence-based management recommendations.